ChemInform Abstract: DNA Modification under Mild Conditions by Suzuki—Miyaura Cross‐Coupling for the Generation of Functional Probes. Issue 6 (11th February 2014) - Lercher, Lukas; McGouran, Joanna F.; Kessler, Benedikt M.; Schofield, Christopher J.; Davis, Benjamin G.
Abstract A new efficient method for Pd‐catalyzed Suzuki—Miyaura cross‐coupling to iododeoxyuridine in DNA is described.